Analytical fluid film force calculation in the case of short bearing with a fully developed turbulent flow. (April 2016) - Ruggiero, Alessandro; Hloch, Sergej; Kozak, Drazan; Valasek, Petr
The main purpose of this paper is to define a methodology to determine the analytical approximate closed-form expression of non-steady fluid film force and of the oil film coefficients for the liquid-lubricated journal bearings in the case of a fully developed turbulent flow regime. The considered model is a symmetrical rigid rotor supported on two lubricated journal bearings; this paper considers the cases of the short bearing approximation, introducing the turbulence correction flow factors in the classical Reynolds equation. The proposed methodology gives the opportunity to solve in approximate way the equation governing the distribution of pressure in the bearing oil gap and then to obtain the closed-form expressions for the non-steady fluid forces. This approach shows the benefit of minimising the calculation time required for the non-linear dynamic analysis of rotors on turbulent journal bearings without any significant loss of accuracy giving a better readability of the parameter involved on the system behaviour.